Effective ways to reduce red tape at UPM - The Star, Cindy Yeoh (2007)
Universiti Putra Malaysia (UPM) was awarded the Finance Management Quality Award (Anugerah Kualiti Pengurusan Kewangan) at the recently held Public Sector Quality Award (AKSA) 2007 ceremony.